Prenatal exposure of female mice to perﬂuorononanoic acid delays pubertal activation of the reproductive endocrine axis through enhanced hepatic FGF21 production. (April 2021) - Zhang, Yajie; Xu, Ye; Ding, Hong; Yu, Wenfeng; Chen, Ling
Abstract: The developmental toxicity of perﬂuorononanoic acid (PFNA), a ubiquitous environmental contaminant, has been associated with the activation of PPARα. This study investigated influence of prenatal exposure to PFNA in pubertal activation of reproductive endocrine axis in female mice and explored underlying molecular mechanisms. Herein, we show that when PFNA (3 mg kg −1 body weight) was orally administered during gestational days 1–18, dams showed an increase in liver weight and hepatic FGF21 synthesis via PPARα activation, and their female offspring (PFNA mice) showed an increase in liver weight and hepatic FGF21 synthesis from postnatal day (PND) 1 to PND21, which were corrected by the administration of the PPARα antagonist GW6471 from PND1-14 (pup-GW). Expression of vasopressin (VAP) in the hypothalamic suprachiasmatic nucleus (SCN) was reduced in PND14-30 PFNA mice, and could be rescued by pup-GW. Pubertal activation of kisspeptin neurons in anteroventral periventricular nucleus (AVPV) and hypothalamic GnRH neurons in PND21-30 PFNA mice was obviously suppressed, but were recovered by pup-GW or PND21-30 application of VAP. The times of vaginal opening and first estrus were delayed in PFNA mice with a decrease in ovary size and the numbers of primary, secondary and antral follicles, and corpora lutea, which were relieved by pup-GW or application of VAP. The findings indicate that prenatal exposure to PFNA through increased FGF21 production in postnatal female offspring impedes postnatal activation of SCN-VAP neurons, which suppresses pubertal onset in AVPV-kisspeptin neurons and reproductive endocrine axis, leading to delayed puberty and dysfunction of ovaries. Graphical abstract: The hypothesis of molecular mechanisms underlying prenatal exposure of PFNA caused delayed puberty and dysfunction of ovaries. ↑: increase; ↓: decrease. Image 1 Highlights: Prenatal exposure of female mice to PFNA increases hepatic FGF21 synthesis. PFNA-increased PPARα-FGF21 impedes postnatal activation of SCN-VAP neurons. Inactivation of VAP neurons suppresses pubertal onset of AVPV-kisspeptin neurons. Increased PPARα-FGF21 disturbs reproductive endocrine leading to delayed puberty. Pubertal inhibition of reproductive endocrine axis causes dysfunction of ovaries.